Motivasi Perilaku dan Bina Potensi Warga Desa Teluk Lecah Kecamatan Rupat Kabupaten Bengkalis Riau - Herispon; Harwina, Yulia; Fachri, Rizqi; Rofidah, Siti; Hendra, Teguh; Dehotman, Khornelis; Herman, Herman (Indra Institute Research & Publication, 2024)
The implementation of community service (PKM) by STIE Riau lecturers has revealed that the main issues local communities face are those related to roads, infrastructure, transportation, education, health, income inequality, employment, poverty, and unemployment, as well as issues with electricity and communication networks. The STIE Riau PKM team carried out this effort as inspiration and enlightenment in thinking to improve the economic level of households. The team held meetings, discussions, and continued with training in making liquid dishwashing soap. They also symbolically planted mangrove seedlings with the village head and residents on the coast of Teluk Lecah Village